2019
DOI: 10.2174/1389200219666180523102920
|View full text |Cite
|
Sign up to set email alerts
|

Application of Traditional Chinese Herbal Medicine By-products as Dietary Feed Supplements and Antibiotic Replacements in Animal Production

Abstract: Misuse of synthetic antibiotics in livestock leads to the transfer of antibiotic resistant pathogens into humans and deposits toxic residues in meat and milk. There is therefore an urgent need for safe and viable alternative approaches to improve the nutrition and wellbeing of farm animals. An alternative source that has been widely exploited is traditional Chinese herbal medicine (TCHM). These herbal medicines are an important part of the healthcare system in many Asian countries. Such herbs contain several b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
41
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 81 publications
(43 citation statements)
references
References 75 publications
2
41
0
Order By: Relevance
“…It has been known that overused antibiotics in animal feed could lead to the development of drug-resistant bacteria and drug residues as threats to human health, so they have been phased out as growth promoters in many countries (12)(13)(14). On the other hand, there is increasing value in finding natural and harmless feed additives to strengthen the immune system and fight against various diseases, thus new antibiotic substitution strategies and alternative feed additives such as microecological preparations and traditional herbal medicine are currently increasing in popularity (15)(16)(17). It reported that the dietary supplementation with propionibacteria promoted mucus secretion characterized by rising goblet cells counts, neutral mucin production, and the longer villus-crypt units.…”
Section: Discussionmentioning
confidence: 99%
“…It has been known that overused antibiotics in animal feed could lead to the development of drug-resistant bacteria and drug residues as threats to human health, so they have been phased out as growth promoters in many countries (12)(13)(14). On the other hand, there is increasing value in finding natural and harmless feed additives to strengthen the immune system and fight against various diseases, thus new antibiotic substitution strategies and alternative feed additives such as microecological preparations and traditional herbal medicine are currently increasing in popularity (15)(16)(17). It reported that the dietary supplementation with propionibacteria promoted mucus secretion characterized by rising goblet cells counts, neutral mucin production, and the longer villus-crypt units.…”
Section: Discussionmentioning
confidence: 99%
“…Traditional Chinese medicines have been recognized as good feed additives in improving animal production performance, immunity, and disease resistance [ 19 , 20 ]. Licorice, a perennial herb, has well-known detoxifying effects [ 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…Traditional Chinese herbal medicine contains numerous biologically active compounds, which can provide various nutritional and health bene ts to animals, so it can be used as a feed additive (Abdallah et al 2019). As a feed additive, purslane is especially worthy of attention in enhancing nutrition, regulating metabolism and promoting the digestion and absorption of nutrients in animals.…”
Section: Introductionmentioning
confidence: 99%